Lingkungan Pendidikan (bi’ah at-tarbawiyah) Perspektif Islam (Tinjauan Ontologis, Epistimologis, Aksiologis Al-Qur’an Dan Hadits Tematik) - Amru Almutasim (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
A comfortable environment and support the implementation of an education is needed and also contribute to the achievement of desired educational goals. Similarly in the Islamic education system, the environment must be created in accordance with the characteristics of Islamic education itself. In educational literature, the environment is usually equated with institutions or educational institutions. Although this study is not explicitly described in the Qur'an, there are some cues indicating the existence of the educational environment. Therefore, in the study of Islamic education, the educational environment received attention. Humans are social and will shape their own environment because humans are one of the subjects discussed, especially those relating to the origin of the concept of creation, human position and purpose in life. This is something that is natural because the Qur'an is believed by Muslims as the word of Allah intended to and for humans.